Susceptibility of winter crops to Pratylenchus brachyurus and effect on the nematode population in the maize crop - Chiamolera, Fernando M.; Dias-Arieira, Claudia R.; de Souto, Eliezer R.; Biela, Fabio; da Cunha, Tatiana Pagan L. [UNESP]; Santana, Simone de Melo; Puerari, Heriksen H. (Organization Trop Amer Nematologists, 2012)
The aim of this study was to evaluate the susceptibility of winter crops to Pratylenchus brachyurus and their effect on the population of phytonematodes in the maize. To study the effect of the plants on nematodes, an experiment was set up in sandy, naturally-infested soil. The area was divided into strips, consisting of six blocks of 16 treatments, with eight winter treatments, subdivided on the basis of the fertilizer used (organic: bird litter, and synthetic: NPK). The initial nematode population was determined by sampling the soil (100 cm(3)) and weeds (10 g of root). The winter treatments put in place (bristle oats, chickpea, vetch bean, common bean, oilseed radish, wheat, intercropped bristle oats + oilseed radish and fallow), and the nematode population determined 100 days after sowing. Subsequently, two maize crops (summer and short season) were planted, and the nematode population in the soil and roots determined during crop full bloom. To evaluate the susceptibility of winter crops to nematodes, an experiment was conducted under controlled conditions, determining the nematode reproduction factor (RF) in the treatments described above. Both in the field and under controlled conditions, it was observed that the bristle oats, oilseed radish and intercropped oats + oilseed radish exhibited lower reproduction rates for P. brachyurus. In the field, lower population of nematodes was observed with the application of bird litter. Under controlled conditions, the highest RF were observed in the fallow plot and under common bean and chickpea, in that order.
Keywords: bristle oats; chickpea; vetch bean; Bean; oilseed radish; wheat; Management; Root lesion nematodes